Online Electrochemical Impedance Spectroscopy (EIS) estimation of a solar panel. (May 2017) - Varnosfaderani, Mina Abedi; Strickland, Dani
Abstract: Electrochemical Impedance Spectroscopy (EIS) techniques are useful tools for being able to look at the characterisation of solar panels under different conditions and/or with different material components. However EIS analysis is mostly undertaken offline with bespoke equipment. This paper describes a method of undertaking EIS measurement on-line without the use of additional equipment by manipulating the control of the solar panel connected dc-dc power electronic converter. The power electronic control is used to inject an additional low-frequency signal into the circuit and then sweep this frequency across a range to replicate the functionality of the EIS without the need for a separate excitation circuit while maintaining full operational functionality. This paper describes the methodology and presents some experimental results compared with EIS results under the same conditions to illustrate the concept. Highlights: Online electrochemical impedance spectroscopy measurement of the solar panel. The solar panel connected power electronic converter can be used to perform this task. The switching of the converter is manipulated to generate low frequency excitation signals in addition to normal operation.